2018
DOI: 10.1101/302307
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The mechanical impact of col11a2 loss on joints; col11a2 mutant zebrafish show changes to joint development and function, which leads to early onset osteoarthritis

Abstract: (max 200 words)Collagen is the major structural component of cartilage and mutations in the genes encoding Type XI collagen are associated with severe skeletal dysplasias (Fibrochondrogenesis and Stickler syndrome) and early onset osteoarthritis. The impact of the lack of Type XI collagen on cell behaviour and mechanical performance during skeleton development is unknown. We studied a zebrafish mutant for col11a2 and evaluated cartilage, bone development and mechanical properties to address this. We show that … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 80 publications
2
20
0
Order By: Relevance
“…When we calculated the ratio between length and width, both mutant lines showed a mild alteration in lower jaw element proportion (figure 7C). Interestingly, in contrast to wildtype and spp1 mutants, the col11a2 mutants exhibited altered joint shape consistent with the predicted OA phenotype in adulthood and as seen in larval jaws previously (figure 7D) (Lawrence, Kague et al, 2018). Measurements of the centrum, neural arch, and haemal arch of the vertebra did not show significant changes in either mutant line (figure 7E-G, figure S8C-G) These histomorphological data show that indeed col11a2 fish showed bone growth defects while spp1 mutants did not.…”
Section: Zebrafish Mutants Of Differentially Expressed Genes Show Skesupporting
confidence: 86%
See 1 more Smart Citation
“…When we calculated the ratio between length and width, both mutant lines showed a mild alteration in lower jaw element proportion (figure 7C). Interestingly, in contrast to wildtype and spp1 mutants, the col11a2 mutants exhibited altered joint shape consistent with the predicted OA phenotype in adulthood and as seen in larval jaws previously (figure 7D) (Lawrence, Kague et al, 2018). Measurements of the centrum, neural arch, and haemal arch of the vertebra did not show significant changes in either mutant line (figure 7E-G, figure S8C-G) These histomorphological data show that indeed col11a2 fish showed bone growth defects while spp1 mutants did not.…”
Section: Zebrafish Mutants Of Differentially Expressed Genes Show Skesupporting
confidence: 86%
“…Wildtype AB/TL (UoB) and AB (RU) strains were used. Mutant lines (AB/TL background, UoB) have been previously described; col11a2 sa18324 carries a nonsense mutation causing a premature stop codon at tyrosine position 228 (ENSDART00000151138.3), henceforth called col11a2 Y228X (Lawrence et al, 2018) and spp1 carrying a deletion leading to a frameshift resulting in a premature stop codon nonsense mutation at proline position 160 (ENSDART00000101261.6), henceforth called spp1 P160X (Bevan, Lim et al, 2020). Transgenic lines are listed in the Supplemental Methods.…”
Section: Zebrafish Husbandry Mutant and Transgenic Linesmentioning
confidence: 99%
“…Recent data has shown that zebrafish can be used to study the development of synovial joints and osteoarthritis. Mutations in col11a2 in zebrafish leads to joint pathologies reminiscent of early‐onset osteoarthritis in humans . Further, as in humans and mice, zebrafish lubricin or proteoglycan‐4b ( prg4b ) expression was found within some joint regions, such as articular chondrocytes in the jaw .…”
Section: Disease Applicationsmentioning
confidence: 99%
“…Scale bar = 100 μm. Images in b and c previously published in (Lawrence et al 2018 ). d–f Ventral paraffin sections of 5 dpf craniofacial skeleton stained with Safranin O ( d ) to show proteoglycans, Masson’s trichrome ( e ) to show the presence of collagen, and alcian blue ( f ) to show the presence of glycosaminoglycans in the chondrocyte ECM which makes up the cartilage.…”
Section: Prospects For Using Zebrafish As a Model For Mechanically Mementioning
confidence: 99%